Essays on macroeconomic policy and growth in India - Acharya, Shankar (New Delhi, 2006)
This collection deals with various aspects of economic reforms undertaken in India since the early 1990s, with a special emphasis on economic growth. The essays underscore the remarkably swift turnaround in the Indian economy from crisis condition in 1991 to good health by 1995. The chapter focus first on policies and performance, and move on to major areas that received government attention, from fiscal consolidation to management of water resources.
Keywords: Macroeconomic policy